2015
DOI: 10.1007/s11295-015-0854-1
|View full text |Cite
|
Sign up to set email alerts
|

Five decades of growth in a genetic field trial of Douglas-fir reveal trade-offs between productivity and drought tolerance

Abstract: To select suitable planting stock for reforestation under uncertain future climates, information about tolerances of genotypes to different climate conditions is necessary. One useful approach is to combine dendrochronological research with common garden experiments to quantify genotype by environment interactions observed over time. Here, we assess the response of Douglas-fir provenances planted in a common environment to climate variation over five decades using treering analysis and historic height data. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 47 publications
(54 reference statements)
2
38
0
Order By: Relevance
“…Successful regeneration during drought depends on microsite conditions, including competition from nonpreferred species. However, current practices and guidelines for seed transfer may need to be reconsidered given the potential for locally maladapted genotypes, as well as the possibility of planting more heatand drought-tolerant genotypes (Aitken et al, 2008;Joyce & Rehfeldt, 2013;Montw e et al, 2015). After all, decades of horticultural practice have clearly shown that growth and reproduction of many species well outside their native ranges is possible, suggesting 'assisted migration' is a viable diversity conservation option (e.g., Schwartz et al, 2012).…”
Section: Drought and Forest Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful regeneration during drought depends on microsite conditions, including competition from nonpreferred species. However, current practices and guidelines for seed transfer may need to be reconsidered given the potential for locally maladapted genotypes, as well as the possibility of planting more heatand drought-tolerant genotypes (Aitken et al, 2008;Joyce & Rehfeldt, 2013;Montw e et al, 2015). After all, decades of horticultural practice have clearly shown that growth and reproduction of many species well outside their native ranges is possible, suggesting 'assisted migration' is a viable diversity conservation option (e.g., Schwartz et al, 2012).…”
Section: Drought and Forest Managementmentioning
confidence: 99%
“…Changing temperatures and precipitation patterns will produce novel combinations of drought frequency, intensity, and seasonality (Wehner et al, 2011;Dai, 2012). Tree populations can disperse and adapt to local climates, including drought stress (Savolainen et al, 2007;Aitken et al, 2008;Montw e et al, 2015). As tree populations arrive in new locations, they interact with existing populations and form new communities.…”
Section: Introductionmentioning
confidence: 99%
“…As productivity and drought tolerance was negatively related in the US population, we had expected a similar growth versus drought tolerance trade-off in the northern population. Recent research has indicated a link between cold adaptation and drought adaptation in seedlings (Bansal et al, 2015a,b) and mature trees of Douglas-fir (Montw e et al, 2015). Cold-adapted trees also invest into thicker cell walls and narrower lumen sizes that are more resistant to freeze-thaw-induced embolisms (Schreiber et al, 2013a,b).…”
Section: Boreal Provenances Appear At Riskmentioning
confidence: 99%
“…Assisted migration involves changing the genetic composition of plant populations by moving seed material to climate regions where they are anticipated to be well adapted in the future 2 , 3 , 10 , 11 . For example, transferring seeds from southern, drought-tolerant tree populations may help more northern forests adapt to drier, warmer conditions 2 , 3 , 13 , 14 . However, there are concerns that assisted migration may not be successful and lead to unintended consequences 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%